The influence of human resource practices on teachers' job satisfaction - Fuzi, Intan Fazlin; Yuzi Fuzi, Muhammad Alif (International Business Education Journal, 2019)
The purpose of this study is to determine the influence of human resource (HR) practices namely training, career development, performance appraisal and compensation on teachers’ job satisfaction. Quantitative correlational method was used and data were collected by using questionnaires from teachers pursuing their studies in a public university in Malaysia. The samples were selected by using simple random sampling technique. Upon receiving 148 returned questionnaires, data was cleaned and missing values were amputated by using mean. Data were then analysed by using multiple regression analysis. The findings of this study revealed that teachers were generally satisfied (mean>3.69) with all of the HR practices. However, only training (β=0.326, p-value